„Ich mach mir keine Sorgen …!“$aWie 4- bis 8-jährige Kinder krebskranker Eltern im Berkeley Puppet Interview psychische Symptome selbst einschätzen - Koch, Gabriele; Dieball, Stefanie; Falk, Carina; Weis, Sascha; Brähler, Elmar; Romer, Georg; Bergelt, Corinna; Keller, Monika; Flechtner, Hans-Henning; Weschenfelder- Stachwitz, Heike; Resch, Franz; Klitzing, Kai von; et al. (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2014)
“I do Not Worry About …!” How the Berkeley Puppet Interview may Reveal Self-Report of Psychological Symptoms of 4 to 8 Years Old Children Exposed to Parental Cancer. The Berkeley Puppet Interview (BPI) enables us to investigate psychological symptoms of children aged four to eight years under a multi-informant perspective by the means of self and parent report measures. 45 families with one parent suffering from cancer have been examined with regard to internalizing and externalizing symptoms of the children. Results have been compared to two different age-appropriate samples (Swiss preschool study of Basel and German KiGGS study). A small, highly selective sample of twelve children aged four to eight years could have been examined both from the self and parent perspective. Our results show, that four to eight year old children of cancer patients do not differ from other children of the same age in the way they express emotional symptoms in the BPI, but they are judged more emotionally burdened than other children by their parents (SDQ). Self and parent report do not significantly correlate. It seems as if parents in families struck by a cancer disease see their children’s emotional symptoms more pronounced than the children themselves do express in the puppet interview. Implications for clinical and research practice will be discussed.
Gesehen am 02.06.2022